2021
DOI: 10.1186/s41938-021-00417-2
|View full text |Cite
|
Sign up to set email alerts
|

On the potential of Bacillus aryabhattai KMT-4 against Meloidogyne javanica

Abstract: Background Nematodes (Meloidogyne spp.) are a major reason behind the global crop yield reduction. The bacterial strain KMT-4 was isolated from nematode-affected tomato (Solanum lycopersicum) rhizosphere at research farms, Hisar, India, and screened for its biocontrol potential against root-knot nematode Meloidogyne javanica as well as checked for its effect on plant growth and yield. Results The bacterium KMT-4 was identified as Bacillus aryabhatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Several studies and patents report Bacillus cells or endospores as biological control agents, particularly against root-knot nematodes from the Meloidogyne genus; however, none of them surpassed the effectiveness reported here for B. paralicheniformis TB197. For example, the percent reduction in GI in field assays through the use of Bacillus altitudinis AMCC1040 ( Wang et al, 2021 ), B. subtilis Bs-1, B. cereus Bc-cm103 ( Cao et al, 2019 ), B. aryabhattai KMT-4 ( Yin et al, 2021 ), B. velezensis Bv-25 ( Antil et al, 2021 ), B. marisflavi CRB2 ( Tian et al, 2022 ), B. subtilis CRB7 and B. methylotrophicus ( Gowda et al, 2022 ) was <70%.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies and patents report Bacillus cells or endospores as biological control agents, particularly against root-knot nematodes from the Meloidogyne genus; however, none of them surpassed the effectiveness reported here for B. paralicheniformis TB197. For example, the percent reduction in GI in field assays through the use of Bacillus altitudinis AMCC1040 ( Wang et al, 2021 ), B. subtilis Bs-1, B. cereus Bc-cm103 ( Cao et al, 2019 ), B. aryabhattai KMT-4 ( Yin et al, 2021 ), B. velezensis Bv-25 ( Antil et al, 2021 ), B. marisflavi CRB2 ( Tian et al, 2022 ), B. subtilis CRB7 and B. methylotrophicus ( Gowda et al, 2022 ) was <70%.…”
Section: Discussionmentioning
confidence: 99%
“…The heatmap of the top 20 bacterial ( Figure 8 ) and fungal taxa ( Figure 9 ) indicated that B. aryabhattai was the most abundant bacterial species present in this sample, while an unidentified species of the Hypocreales order was the most abundant fungal strain. The occurrence of B. aryabhattai could explain the highest suppressiveness of M. enterolobii , as this bacterial species was shown to be very effective when it comes to nematode biocontrol; previous studies proved the nematicidal potential of this bacteria against M. javanica and the soybean cyst nematode ( Heterodera glycines ) [ 62 , 63 ]. Observations from these studies suggested that B. aryabhattai might prevent the hatching of J2 from eggs and reduce the number of H. glycines cysts and M. javanica galls on roots, while enhancing plant growth and J2 mortality in soil [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of B. aryabhattai could explain the highest suppressiveness of M. enterolobii , as this bacterial species was shown to be very effective when it comes to nematode biocontrol; previous studies proved the nematicidal potential of this bacteria against M. javanica and the soybean cyst nematode ( Heterodera glycines ) [ 62 , 63 ]. Observations from these studies suggested that B. aryabhattai might prevent the hatching of J2 from eggs and reduce the number of H. glycines cysts and M. javanica galls on roots, while enhancing plant growth and J2 mortality in soil [ 62 , 63 ]. The analyses showed the presence of several hypocrealean fungi that are known for their nematode biocontrol potential.…”
Section: Discussionmentioning
confidence: 99%
“…During the pot experiment, the bacteria were able to reduce eggs by 73% and plant root galls by 80% compared to the chemically treated and untreated plants. Among the mechanisms, the bacterial strain was able to exhibit plant growth promoting traits such as indo-3-acetic acid (IAA), siderophores, ammonia, hydrogen cyanide, chitinase, and secondary metabolites with nematocidal activity and contributed to the suppression of nematodes [120]. Six rhizosphere bacterial isolates were studied for their ability to suppress and kill plant parasitic nematodes in the laboratory and greenhouse.…”
Section: Plant Growth Promotion Bacteria (Pgpb)mentioning
confidence: 99%
“…Many synthetic chemicals of non-organic origin are banned in many countries. These chemicals include barbofuran, carbosulfan, ethylene dibromide, and chloropicrin [120]. To achieve sustainable agriculture, researchers are formulating beneficial microbiomes and their metabolites into biopesticide useful in plant production [143].…”
Section: Biocontrol Of the Plant Parasitic Nematodes Using Bio-products Of Microbial Originmentioning
confidence: 99%